Application of edible coatings in minimally processed sweet potatoes (Ipomoea batatas L.) to prevent enzymatic browning - Ojeda, Gonzalo Adrian (2014)
Summary: To control browning phenomenon, an edible coating of cassava starch along with ascorbic acid (AA) (combined treatment) was applied to minimally processed sweet potatoes var cv. 'Blanca Correntina'. The samples were stored at 4 °C for 16 days, and the activities of polyphenol oxidase, peroxidase and phenylalanine ammonia lyase were studied; also, surface colour, antioxidant capacity, ascorbic acid, chlorogenic acid content were evaluated. The combined treatment showed a beneficial impact on the quality of the product, avoiding browning when compared with untreated samples and individual treatments (coating without AA or immersion in AA solution). The improvements were evidenced by the absence of changes in hue, minor changes in a* parameter and a major inhibitory effect of AA on the activity of the three enzymes. Ascorbic acid content and antioxidant capacity increased (P < 0.05). The combined treatment not only was effective in preventing enzymatic browning but also retained freshness and improved nutritional value.